Penanaman Pohon Alpukat Sebagai Penciri Desa Bululawang Sebagai Desa Wisata - Endang Sungkawati; Ni Wayan Suarniati; Roy Anugerah; Nova Dwi Hernanik (Universitas Mathla'ul Anwar Banten, 2022)
PLANTING AVOCADO TREES AS A CHARACTERISTIC OF BULULAWANG VILLAGE AS A TOURISM VILLAGE. Community Empowerment activities in Bululawang village aim to create a tourist village that has characteristics that distinguish it from other tourist attractions. The development of tourism in Bululawang village as a tourist village considers the advantages and benefits for the Bululawang community. It is hoped that the formation of a tourist village will have a positive impact on the people, which can create wide employment opportunities. Community service is carried out through several activities, namely: 1) environmental education; 2) formation of pokdarwis; 3) planting avocado seeds 4) assistance in making tourist attractions and 5) management assistance. Pokdarwis in collaboration with the Gapoktan (Farmers Group), planted avocado trees as a characteristic of Bululawang village. The results of this community service encourage Pokdarwis members and Gapoktan members to realize Bululawang Village as a tourist village, raise awareness of the need for environmental protection, increase community commitment, and the commitment of the village government to provide full support to the establishment of a tourist village.